The Relationships of Aerosol Deposition, Lung Size, and the Rate of Mucociliary Clearance - Gerrard, Christopher S.; Gerrity, Timothy R.; Yeates, Donovan B. (Archives of environmental health, 1986)
Although the effect of deposition pattern of an inhaled aerosol upon subsequent mucociliary clearance is well recognized, the influence of lung size on the rate of clearance has not been clearly defined. To examine the relationships of lung size in terms of the forced vital capacity (FVC) and aerosol deposition pattern to the rate of mucociliary clearance, we measured lung retention of an inhaled 8-μm aerosol for 120 min using a gamma camera in 13 healthy nonsmoking volunteers. The deposition pattern of the inhaled aerosol was defined in terms of the initial skew of the distribution of retained activity within the right lung (skew) and the percent retained at 24 hr (R24). Multiple regression analysis showed that FVC was responsible for approximately 36% of the variability in bronchial retention with time, with a lesser contribution from variations in deposition pattern (skew and R24). Mucociliary clearance was significantly slower (i.e., greater bronchial retention) in male subjects than in female subjects which can probably be attributed to the differences in FVC. Variations in lung sizes as well as deposition pattern should therefore be considered when making between subject comparisons of the mucociliary clearance rate.